The Legal Reconstruction of The Audit of Health Claims In BPJS Health Claim Refund Based On Justice Principles - Budiono, Heri (Journal Research of Social Science, Economics, and Management, 2025)
This research explores the need for legal reconstruction in the audit system of BPJS Health claim refunds, focusing on the principles of justice. The study identifies the inequities in the current claims audit process, especially in remote regions where rigid procedural requirements and technological reliance create significant challenges for healthcare facilities. Using a normative research methodology, the study analyzes existing regulations and proposes a reconstruction based on fairness, efficiency, and equity. Findings suggest that the current system often results in financial instability for hospitals and inefficiencies in service provision due to procedural inconsistencies. The proposed legal reconstruction aims to address these issues by creating a more responsive and just audit system, ensuring that all stakeholders, including hospitals in underserved areas, are treated equitably. This study emphasizes the importance of balancing administrative compliance with the needs of healthcare providers, ultimately fostering a more sustainable and effective healthcare system. By incorporating progressive legal theory, the research highlights how legal reforms can improve the claims audit process, benefiting both healthcare providers and BPJS participants.